Peningkatan Kemampuan Kader Kesehatan dalam Melakukan Pendampingan di Masyarakat Tentang ASI dan MP-ASI - Mochammad Bagus Qomaruddin; Shrimarti Rukmini Devy; Muji Sulistyowati; Rachmah Indawati (Penerbit Goodwood, 2026)
Purpose: Breastfeeding and complementary feeding are very important for maternal and infant health. However, the low exclusive breastfeeding and early complementary feeding is a challenge in health programs. The purpose of community service is an effort to improving health volunteer’s competency in community mentoring for breastfeeding and complementary feeding. Methodology: Mentoring is an approach to bridge the need for knowledge and improve the skills of health volunteers. The form of activity is to improve health volunteer’s competency by providing knowledge and skills in health services. Results: The knowledge and skills of providing health services to pregnant women are very good. Counseling as an effort to provide insight to Health volunteers about breastfeeding and complementary feeding. And mentoring as an effort to train self-readiness or get used to carrying out tasks in the community. In addition, the attitude of pregnant women shows a positive attitude. This activity can create good relationships in the community. Limitations: Participating health volunteers was very limited only two individuals making it difficult to generalize the findings to broader health care populations in other regions. Contributions: This program made a concrete contribution by improving the knowledge and skills of health volunteers in delivering counseling on breastfeeding and complementary feeding to pregnant women in the local community. Conclusions: This activity offers hope for health volunteers to enhance their knowledge and skills in supporting health service programs. Mentoring can establish networks between higher education institutions and partners, fostering positive interactions between health volunteers and the community.